Extracellular Vesicles From the Human Natural Killer Cell Line NK3.3 Have Broad and Potent Anti-Tumor Activity - Cochran, Allyson M.; Kornbluth, Jacki (Frontiers in Cell and Developmental Biology, 2021)
Natural killer (NK) cells are critical mediators of immune function, responsible for rapid destruction of tumor cells. They kill primarily through the release of granules containing potent cytolytic molecules. NK cells also release these molecules within membrane-bound exosomes and microvesicles – collectively known as extracellular vesicles (EV). Here we report the characterization and anti-tumor function of EVs isolated from NK3.3 cells, a well described clonal normal human NK cell line. We show that NK3.3 EVs contain the cytolytic molecules perforin, granzymes A and B, and granulysin, and an array of common EV proteins. We previously reported that the E3 ubiquitin ligase, natural killer lytic-associated molecule (NKLAM), is localized to NK granules and is essential for maximal NK killing; here we show it is present in the membrane of NK3.3 EVs. NK3.3-derived EVs also carry multiple RNA species, including miRNAs associated with anti-tumor activity. We demonstrate that NK3.3 EVs inhibit proliferation and induce caspase-mediated apoptosis and cell death of an array of both hematopoietic and non-hematopoietic tumor cell lines. This effect is tumor cell specific; normal cells are unaffected by EV treatment. By virtue of their derivation from a healthy donor and ability to be expanded to large numbers, NK3.3 EVs have the potential to be an effective, safe, and universal immunotherapeutic agent.